(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Road networks play a crucial role in fostering economic growth and development. This current research focuses on examining and identifying changes in land use and land cover at a small scale. The study utilizes a GIS-based approach, analyzing Landsat imagery taken before (2019) and after (2022) a road widening project. The results reveal a dynamic transformation in land use and land cover in Anantnag, Kashmir, as a consequence of the road widening. This includes the introduction of new land use categories and significant alterations in the overall land use pattern in the area.